Pendampingan Pelaksanaan Uji Kompetensi Keahlian Mandiri Bidang Bisnis Daring dan Pemasaran - Nurendah, Yulia (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
UKK (Skill Competency Test) is implemented to fulfill the mandate in government regulation number 19 of 2005 concerning national education standards. National education standards (SNP) are the minimum criteria for the education system throughout the jurisdiction of the Unitary State of the Republic of Indonesia. The Mentoring Activity for the Implementation of the Independent Skill Competency Test for Online Business and Marketing Competencies was carried out at SMK Kamandaka on March 5-6, 2024 which was held for 2 days. The number of Participants in the Independent Skill Competency Test for Online Business and Marketing Competencies at SMK Kamandaka was 24 Participants on the first day and 12 Participants on the second day. Keywords: UKK, Online Business and Marketing